Klasterisasi Kecamatan di Jabodetabek Berdasarkan Potensi Pengembangan Pasangan Tanaman Sayuran Tahun 2020 - Ahmad, Hafidlotul Fatimah; Soim, Ahmad (Seminar Nasional Official Statistics, 2024)
Per capita vegetable consumption in Indonesia has increased from 54,291 kg in 2018 to 58,477 kg in 2021. This increase highlights the need for more efficient vegetable cultivation systems, such as polyculture, where multiple types of plant are grown in one location. However, the suitability of plants for polyculture systems has traditionally been determined using approximate methods. To address this, the research utilizes the ECLAT algorithm with vegetable production data from BPS to identify which crops are frequently grown together in each sub-district. Furthermore, to identify areas with potential for developing vegetable crop pairs, clustering was carried out using the K-Medoids algorithm. The findings reveal that the most commonly paired vegetable plants in sub-district of Greater Jakarta are "Cucumber & Long Beans" and "Spinach & Kale". These sub-districts were grouped based on crop pair production into 3 clusters with high, medium and low production levels. The research concludes that the highest level of vegetable crop pair production is in Bogor Regency.